2009
DOI: 10.1002/ajpa.21078
|View full text |Cite
|
Sign up to set email alerts
|

Near Eastern Neolithic genetic input in a small oasis of the Egyptian Western Desert

Abstract: The Egyptian Western Desert lies on an important geographic intersection between Africa and Asia. Genetic diversity of this region has been shaped, in part, by climatic changes in the Late Pleistocene and Holocene epochs marked by oscillating humid and arid periods. We present here a whole genome analysis of mitochondrial DNA (mtDNA) and high-resolution molecular analysis of nonrecombining Y-chromosomal (NRY) gene pools of a demographically small but autochthonous population from the Egyptian Western Desert oa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…It seems likely that some JT lineages, especially T ones, were introduced into Northeast Africa before the Neolithic, following Late Glacial population expansions in the Near East/Arabia. Then, locally they could have been involved in population expansions in the Neolithic period, leading to signs of autochthonous founder effects, such as the one detected in the El-Hayez oasis (400 km southwest of Cairo) for sub-haplogroup T1a2a [52]. …”
Section: Resultsmentioning
confidence: 99%
“…It seems likely that some JT lineages, especially T ones, were introduced into Northeast Africa before the Neolithic, following Late Glacial population expansions in the Near East/Arabia. Then, locally they could have been involved in population expansions in the Neolithic period, leading to signs of autochthonous founder effects, such as the one detected in the El-Hayez oasis (400 km southwest of Cairo) for sub-haplogroup T1a2a [52]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, the conservation of the high frequency and remarkable internal variability of T1 haplotypes within the distant and relatively isolated Egyptian oasis of el-Hayez led to an estimation of local expansion at around 5138 ± 3633 YBP. 37 There are no indications yet of the ages of local expansions in the more central and western regions of North Africa, which could contribute further insights for its absence in the Tuareg population as a whole.…”
Section: Genetic Diversity Of Tuareg Nomads L Pereira Et Almentioning
confidence: 97%
“…It has been shown that these non-Lbut nonetheless already African-clades are present in higher frequency mainly in nomadic pastoralists such as the Fulani (U5) or Tuareg (H1, H3, and V) (Ottoni et al, 2009;Pereira et al, 2010a;Černý et al, 2011b), and that the most probable timeframe for their arrival to the south of the Sahara is 3-9 ka (Pereira et al, 2010a). As a result of the subsequent Neolithic development in the east Mediterranean, other mtDNA lineages originally from the Near East, such as J and T, enriched the North African maternal gene pool especially in its eastern parts (Coudray et al, 2009;Kujanová et al, 2009), but did not reach sub-Saharan locations. In Daza, we identified only M1 and U6 (no H1, H3, V, or JT) clades, suggesting rather the pre-Neolithic formation of their maternal gene pool.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogeographic analysis and whole genome sequencing of L3f3 (Černý et al, 2009) showed not only that this clade is restricted to the LCB geographical region, where it expanded ∼9 ka, but that it prevails in its Chadic speaking peoples. Because L3f3 has deep roots in East Africa, where its mother clade L3f had already emerged ∼50 ka (Soares et al, 2012), we suggested a possible eastern link of this clade, likely related to the linguistically inferred westward migration of Cushitic pastoralists (Blench, 1999;Černý et al, 2009). …”
Section: Introductionmentioning
confidence: 99%